Socio-pedagogical prerequisites for the establishment of educational institutions in Kazakhstan - Smailova, Feruza; Galiya Kulzhanbekova, Aida Nurbayeva,; Gulzhan Kalambayeva, Lelya Bugenova, (Opción)
Acquisition of sovereignty by Kazakhstan, democratic transformations taking place in society, the task of becoming one of the 50 developed countries of the world, the need to communicate with foreign partners, the market conditions make it vital the mastery of a foreign language. This, in turn, sets the task of improving teaching a foreign language, studying the development of the phenomenon under study, identifying and tracking the changes that occurred in this process depending on the social demand.